2010
DOI: 10.9755/ejfa.v22i1.4904
|View full text |Cite
|
Sign up to set email alerts
|

Forage yield and quality potential of winter cereal-vetch mixtures<br>under rainfed conditions

Abstract: Livestock in rainfed area of Pothwar often faces green fodder scarcity during winter months and thus has to survive on cereal residues of previous crops such as wheat straw, summer sorghum, corn stalk etc. which are not rich source of protein and digestible nutrients. The basic objective of this experiment is to produce more fodder for livestock production and food for community. The investigations were carried out to evaluate the yield and quality of oat (Avena sativa L.), barely (Hordeum vulgare) and wheat (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 12 publications
1
15
1
1
Order By: Relevance
“…Similar effect of harvesting was observed on the dry matter yield of legumes. The increase in forage yield with delayed harvesting has also been reported by other workers [5,7,17].…”
Section: Dry Matter Yield Of Millet and Legumes Mixturesupporting
confidence: 84%
“…Similar effect of harvesting was observed on the dry matter yield of legumes. The increase in forage yield with delayed harvesting has also been reported by other workers [5,7,17].…”
Section: Dry Matter Yield Of Millet and Legumes Mixturesupporting
confidence: 84%
“…From Table 2 it can be seen that, at cut I, the highest dry matter was obtained by the common vetch (T10) that was not significantly different from T8 compared to almost all the other treatments. For for both cuts and unlike another studies (Ansar et al, 2010;Alami et al, 2015), no significant differences were recorded between binary and ternary mixtures. This occurrence is not in agreement with the conclusions of Papadopoulos et al (2012), who reported increased forage yields when mixture complexity increased.…”
Section: Dry Matter Yieldcontrasting
confidence: 60%
“…This is because oats shows greater complementarity with vetch because better use nitrogen fixed by the legume on the ground compared to other grasses. Another factor may be the physical ability of species to grow; it has been shown that weight and plant height are higher in oatvetch mixtures than with barley-vetch or wheatvetch (18) , furthermore oats grow better in competition; previous studies indicate that this crop shows a linear increase in competition with vetch as the density increases oat (11) . These qualities allow the oats have better growth and consequently increased production of dry matter (19) .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the CP varied depending on the type of mixture and at what harvesting stage it was evaluated. The highest amount of crude protein was found in the mixtures oat-vetch and triticale-vetch during booting stage; and in terms of seed mixture ratios, the vetch monoculture obtained the highest during the grain mature stage, followed puede ser la capacidad física de las especies en crecer; se ha demostrado que el peso y la altura de la planta son más altos en mezclas de avena-veza que en asociaciones de cebada-veza o trigo-veza (18) , además, la avena se adapta mejor a la competencia; estudios previos indican que este cultivo muestra un incremento lineal en competición con la veza conforme la densidad de la avena incrementa (11) . Estas cualidades le permiten a la avena tener un mejor crecimiento y en consecuencia mayor producción de materia seca (19) .…”
Section: Discussionunclassified